Educational scores: How does Russia fare? - Chiara Amini; Simon Commander (Institute for the Study of Labor (IZA), 2011)
This paper uses two large multi-country datasets on educational scores PISA and TIMSS to examine the performance of Russia in comparative light as well as the factors associated with differences in educational outcomes in Russia. Despite the perception of a positive educational legacy, Russian scores are not stellar and have mostly deteriorated. Using an education production function, we distinguish between individual and family background factors and those relating to the school and institutional environment. We use pooled data, as well as cross sectional evidence, to look at the variation across countries before looking at within-country variation in Russia. We find both in the cross-country estimates as also those using just Russia data that a number of individual and family variables in particular, such as parental educational levels, are robustly associated with better educational outcomes. Institutional variables also matter notably student-teacher ratios and indicators of school autonomy but there are also some clear particularities in the Russian case.
urn:nbn:de:101:1-201110263776
Keywords: H5; I21; I28; J24; O15; P5; 330; human capital; PISA; Bildungsniveau; Bildungsökonomik; Russland